Management - Robbins, Stephen P 1943-; Coulter, Mary K. (Hoboken, NJ : Pearson, 2020)
"This course and this book are about management and managers. Managers are one thing that all organizations--no matter the size, kind, or location--need. And there's no doubt that the world managers face has changed, is changing, and will continue to change. The dynamic nature of today's organizations means both rewards and challenges for the individuals who will be managing those organizations. Management is a dynamic subject, and a textbook on it should reflect those changes to help prepare you to manage under the current conditions. We've written this 14th edition of Management to provide you with the best possible understanding of what it means to be a manager confronting change and to best prepare you for that reality. But not every student aspires to a career in management. And even if you do, you may be five or ten years away from reaching a managerial position. So you might rightly feel that taking a course in management now may be getting ahead of the game. We hear you. In response to these concerns, we've added new material to this book that is important and relevant to everyone working in an organization--manager and non-manager alike. Our "Workplace Confidential" pages identify, analyze, and offer suggestions for dealing with the major challenges that surveys indicate frustrate employees the most. You should find these pages valuable for helping you survive and thrive in your workplace. Surprisingly, this topic has rarely been addressed in business programs. Inclusion in an introductory management course appeared to us to be a logical place to introduce these challenges and to provide guidance in handling them"--
Revised edition of the authors' Management, [2018]
Keywords: Management